2018
DOI: 10.9734/acri/2018/39904
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Lassa Fever and Its Determinants among Traders in Izzi Community in South-East Nigeria

Abstract: Background: Lassa fever is a viral hemorrhagic fever found predominantly in West Africa with the potential to cause approximately 5,000 deaths per year. However, good knowledge of the disease may reduce the infection rate. The study assessed the knowledge of Lassa fever and its determinants among traders in Izzi community Ebonyi State, Nigeria. Methods: A descriptive cross-sectional study was conducted among 248 traders selected by simple random sampling method. Data were collected from respondents who gave th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 8 publications
6
16
1
Order By: Relevance
“…The high awareness of LF could be because of the high sensitization and awareness campaign about the infection during past epidemics in the state[20]. This finding was similar to a previous study byNwonwu et al in Izzi, Ebonyi state[16]. Olowoere et al also reported a poor knowledge of LF by respondents in Ile Ife…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The high awareness of LF could be because of the high sensitization and awareness campaign about the infection during past epidemics in the state[20]. This finding was similar to a previous study byNwonwu et al in Izzi, Ebonyi state[16]. Olowoere et al also reported a poor knowledge of LF by respondents in Ile Ife…”
supporting
confidence: 82%
“…We included all consenting adults who were present at homes at the time of the study while adults who were too sick to participate were excluded. Using the formula for the estimation of sample size for single independent proportion, ðn ¼ Zα 2 pq d 2 ) [15], and the prevalence of good knowledge in an earlier study of 30% [16], Z α of 1.96 at 95% confidence level and a precision of 5%, a minimum sample size of 323 was calculated. After correcting for 10% non-response, a sample size of 356 was used in the study.…”
Section: Study Population and Sampling Techniquementioning
confidence: 99%
“…In a study in a rural community, the majority (79.4%) were also aware of Lassa fever. 11 A similar high proportion of respondents among members of staff 15 and students 16 of a tertiary institution in Nigeria and among adults in a rural community 17 were aware of Lassa fever. Furthermore, in a study in Northeast Nigeria, 59% were aware of Lassa fever.…”
Section: Discussionmentioning
confidence: 92%
“…In a study in a rural community, radio was the major source of information. 11 In studies in other geo-political zones of Nigeria, including South South, 17 North Central 20 and Southwest Nigeria, 19,21,22 mass media remained the major source of information on Lassa fever. This is commendable and could be attributed to the efforts of the government and other agencies in curtailing outbreaks of Lassa fever, since the disease is epidemic prone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation